Dampak ekonomi terhadap kesehatan mental: menelusuri hubungan antara kesejahteraan dan psikologi - Raffi, Muhammad Haidar (Maliki Interdisciplinary Journal, 2025)
A person's mental health is very important and is influenced by many factors, one of which is their financial situation. Research shows that low economic status is associated with increased stress, anxiety, and depression, which adversely affects psychological well-being. Financial uncertainty and poverty worsen an individual's mental condition by limiting access to health services and social support. Economic crises also elevate the rates of mental disorders in society, particularly among vulnerable groups. Understanding the relationship between economics and mental health can assist in creating better policies and programs to enhance mental well-being across different segments of society. Therefore, it is crucial for governments and communities to take broad action, including creating supportive economic policies, increasing access to education, and providing mental health education. These actions are expected to create a better environment where people can improve their mental well-being and mitigate the negative effects of difficult economic conditions.